2021
DOI: 10.1186/s40359-020-00499-x
|View full text |Cite
|
Sign up to set email alerts
|

What factors are most important for the development of the maternal–fetal relationship? A prospective study among pregnant women in Danish general practice

Abstract: Background Development of the maternal antenatal attachment (MAA) constitutes an important aspect of the transition into motherhood. Early identification of women at risk of developing a poor MAA provides possibilities for preventive interventions targeting maternal mental health and the emerging mother-infant relationship. In this study, we investigate the relative importance of an extensive set of psychosocial, pregnancy-related, and physiological factors measured in the first trimester of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 45 publications
(79 reference statements)
1
19
1
3
Order By: Relevance
“…Although not an exclusion criteria per se, the sample does not include women under treatment for significant mental health issues that may jeopardize psychological well-being during pregnancy. Mean MAAS (antenatal attachment) values recently reported from two large, population-based cohorts in Denmark (Ertmann et al, 2021) and Australia (Le Bas et al, 2021) were very similar to those found in our United States-based sample, although MPAS (postnatal attachment) values in our sample were considerably lower than in Australia (Le Bas et al, 2021). An interesting cross-cultural study provides evidence for measurement equivalence of the construct of antenatal attachment across eight low-and middle-income countries and found no differences in mean antenatal attachment levels among six of them (Foley et al, 2021).…”
Section: Limitations and Other Considerationssupporting
confidence: 85%
See 2 more Smart Citations
“…Although not an exclusion criteria per se, the sample does not include women under treatment for significant mental health issues that may jeopardize psychological well-being during pregnancy. Mean MAAS (antenatal attachment) values recently reported from two large, population-based cohorts in Denmark (Ertmann et al, 2021) and Australia (Le Bas et al, 2021) were very similar to those found in our United States-based sample, although MPAS (postnatal attachment) values in our sample were considerably lower than in Australia (Le Bas et al, 2021). An interesting cross-cultural study provides evidence for measurement equivalence of the construct of antenatal attachment across eight low-and middle-income countries and found no differences in mean antenatal attachment levels among six of them (Foley et al, 2021).…”
Section: Limitations and Other Considerationssupporting
confidence: 85%
“…This scale assesses maternal feelings of closeness, preoccupation, and emotionality towards the fetus within the time frame of the previous two weeks of pregnancy (Condon, 1993). It, and the postnatal version, were used in two recent, population-based studies of maternal attachment totaling nearly 3,000 participants (Ertmann et al, 2021;Le Bas et al, 2021). Unlike some other antenatal attachment scales which include feelings about being pregnant, all MAAS items are directed specifically towards the fetus.…”
Section: Maternal Antenatal Attachment Scale (Maas)mentioning
confidence: 99%
See 1 more Smart Citation
“…The mean scores for COVID-19-related worries were 12.02 (SD = 3.70) for health worries, 20.15 (SD = 6.42) for worries regarding impact on pregnancy, and 11.48 (SD = 4.24) for worries regarding access to resources. Finally, participants had an average sum 71.82 (SD = 7.29) out of a total possible score of 90 on the MAAS; a sum of 71 or below, corresponding to less than 80% the maximum MAAS, may be interpreted to represent low antenatal bonding [ 53 ]. The responses for COVID-19-related worries were further examined in Table 3 , with a response of ‘Worried’ or ‘Very Worried’ being considered to represent high levels of concern.…”
Section: Resultsmentioning
confidence: 99%
“…Okres oczekiwania na urodzenie pierwszego dziecka to przygotowawczy etap kształtowania się tożsamości macierzyńskiej (Stern, 1998). Założenia te potwierdzają wyniki duńskiego badania przywiązania matki do dziecka w okresie prenatalnym (Ertmann i in., 2021). Autorzy badania zwracają także uwagę na to, że kobiety posiadające dzieci, kobiety lepiej wykształcone i kobiety starsze wykazują mniejsze zaabsorbowanie dzieckiem w łonie (uzyskały niższe wyniki w skali przywiązania matki do dziecka w okresie prenatalnym MAAS -Maternal Antenatal Attachment Scale), co tłumaczą przypisywaniem przez nie mniejszej wartości macierzyństwu w rozumieniu poczucia spełnienia w tejże roli, a także większemu realizmowi i zaniepokojeniu zmianami zachodzącymi w organizmie w czasie ciąży.…”
Section: Wynikiunclassified